Measurements of gunshot residues by sector field inductively coupled plasma mass spectrometry - Further studies with pistols - Sarkis, Jorge E. Souza; Neto, Osvaldo N.; Viebig, Sonia; Durrant, Steven F. (Elsevier B.V., 2007)
The most popular handgun in Brazil is the single round-barrel caliber 0.38 revolver. In recent years, however, owing to the modernization of police arms and their availability on the legal and illicit markets, pistols have become increasingly popular and currently represent about 20% of police seizures. In a previous paper we presented a novel collection method for gunshot residues (GSR) using a sampling procedure based on ethylenediamine-tetraacetic acid (EDTA) solution as a complexing agent on moistened swabs with subsequent detection using sector field-high resolution-inductively coupled plasma-mass spectrometry (SF-HR-ICP-MS). In the present paper, we discuss the capability of this methodology to identify antimony (Sb), barium (Ba) and lead (Pb) on the hands of volunteers after shot tests with 9 mm and 0.40 in. caliber pistols. Two types of munitions were tested: 9 mm Taurus and clean range. The use of a technique with high sensitivity, such as SF-HR-ICP-MS, permits the identification of low concentrations (less than 1 mu g/L) of metals in firearm residue and constitutes a powerful tool in forensic science. We also discuss the importance of the sampling procedure, including collection from a different body part than the gun hand of the suspect. Comparison of the analytical data obtained allows clear discrimination between samples from the hands of shooters and non-shooters. (C) 2007 Elsevier B.V.. All rights reserved.
Keywords: pistols; gunshot residues; collection; barium; lead; antimony; inductively coupled plasma-mass spectrometry